2011
DOI: 10.1038/npp.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Mechanisms of Treatment in Depression

Abstract: Cognitive abnormalities are a core feature of depression, and biases toward negatively toned emotional information are common, but are they a cause or a consequence of depressive symptoms? Here, we propose a 'cognitive neuropsychological' model of depression, suggesting that negative information processing biases have a central causal role in the development of symptoms of depression, and that treatments exert their beneficial effects by abolishing these biases. We review the evidence pertaining to this model:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
497
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(537 citation statements)
references
References 277 publications
(293 reference statements)
27
497
0
13
Order By: Relevance
“…The presence of emotional biases among patients suffering from depression is well established [11]. Behaviourally, depressed patients show increased processing of negative versus positive emotional information.…”
Section: Cognitive Biases In Depressionmentioning
confidence: 99%
“…The presence of emotional biases among patients suffering from depression is well established [11]. Behaviourally, depressed patients show increased processing of negative versus positive emotional information.…”
Section: Cognitive Biases In Depressionmentioning
confidence: 99%
“…At the neuropsychological level, fronto-limbic disruptions are thought to play a crucial role in cognitive impairments involved in emotion regulation (for reviews, see Pizzagalli, 2011;Roiser, Elliott, & Sahakian, 2012). Key findings from neuroimaging studies have shown that depression is associated with disrupted brain activity in the dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) (Davidson, Pizzagalli, Nitschke, & Putman, 2002;Etkin, Gyurak, & O'Hara, 2013;Pizzagalli, 2011), with decreased activation in these prefrontal areas being related to reduced cognitive control (Collette & Van der Linden, 2002;Smith & Jonides, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoactivity of the DLPFC and hyperactivity of subcortical structures are associated to MDD and its cognitive deficits [14,18]. Moreover, two modalities of impaired cognitive processing are observed in MDD, namely 'cold' and 'hot' cognition, which refer to information processing in the absence or presence of emotional influence, respectively [19].…”
Section: Introductionmentioning
confidence: 99%